Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10461-006-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Children and Pregnancy Risk Behavior among HIV-Infected Men and Women in Uganda

Abstract: To identify ways to improve prevention of mother-to-child transmission (PMTCT) of HIV, we conducted a cross-sectional study of 1,092 HIV-infected men and women attending an AIDS support organization in Jinja, Uganda, between October 2003 and June 2004. Pregnancy risk behavior was defined as having sex without contraceptive or condom. Overall, 42% of participants were sexually active, 33% practiced pregnancy risk behavior, and 18% desired more children. Men were almost four times to want more children than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
122
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 18 publications
25
122
6
Order By: Relevance
“…And nearly 10% of the sero-discordant partners still decided to have a child; the study result showed that, participants whose partner's test result was negative were 63% less likely for fertility decision than with positive result [AOR, 95% CI 0.366 (0.193, 0.907)], (P<0.001). This is in line with other studies conducted in Uganda (11). This could be due to fear of infecting their partner, which could raise an issue of SRH right of PLWHA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…And nearly 10% of the sero-discordant partners still decided to have a child; the study result showed that, participants whose partner's test result was negative were 63% less likely for fertility decision than with positive result [AOR, 95% CI 0.366 (0.193, 0.907)], (P<0.001). This is in line with other studies conducted in Uganda (11). This could be due to fear of infecting their partner, which could raise an issue of SRH right of PLWHA.…”
Section: Discussionsupporting
confidence: 91%
“…Men were found almost twice more likely to decide on fertility than women [AOR, 95%CI, 1.78 (1.15, 2.74)] (p<0.01). This finding is higher than the study conducted in Uganda (16%) and consistence in its pattern in that men were almost four times more likely to want more children than women (11). The study also revealed that current fertility decision among men was lower than a study conducted in Brazil (50.1%).…”
Section: Discussioncontrasting
confidence: 72%
“…[15,16] Some studies have shown HIV-positive status to be associated with low fertility intentions and at the same time low contraceptive use. [17,18,3] In particular, a multi-country analysis of Demographic and Health Survey (DHS) data from nine countries revealed lower contraceptive uptake among HIV-positive women with prior knowledge of their status than counterparts who were HIV-negative in three of the countries included in the study: Zimbabwe, Kenya, and Malawi. [16] The apparent disconnect between fertility desire and contraceptive uptake among HIV-positive women has been attributed to diverse factors ranging from social desirability or stigma surrounding childbearing for HIV-positive individuals [19] to low contraceptive use among HIV-positive women based on the perception that they and their partners were infertile due to HIV infection [20].…”
Section: Introductionmentioning
confidence: 99%
“…HIV transmission risk in patients on HAART is low only if the following conditions are met: the HIV-infected patient is receiving HAART with excellent adherence; patients disclose their HIV status and inquire about HIV status of their sexual partners; the viral load is consistently undetectable for a long time; and no sexually transmitted infections (STIs) are present in either partners. The above conditions are not met in many sub-Saharan African settings, as many studies [56][57][58][59][60][61] report that sub-optimal adherence, high fertility intentions, and risk factors for acquisition of STI (such as multiple sexual partners, and inconsistent condom use) are common. In many settings in sub-Saharan Africa, such as eastern and southern Africa, high-risk behaviors occur in HIV patients before and after initiating HAART [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%